Patient activation levels and socioeconomic factors among the Amazonas population with diabetes: a cross-sectional study - Elisa Brosina de Leon; Hércules Lázaro Morais Campos; Natália Barbeiro Santos; Fabiana Almeida Brito; Fabio Araújo Almeida (BMC, 2024)
Abstract Background The presence of chronic conditions such as type 2 diabetes mellitus (T2DM) requires behavioral lifestyle changes mediated by individuals' motivation for change and adherence to treatment. This study aims to explore activation levels in individuals with T2DM treated in primary care facilities and to identify the association between demographic, clinical, psychosocial factors, and patient activation amongst populations in the Brazilian state of Amazonas. Methods SAPPA is a cross-sectional study conducted in Amazonas, approved by the Universidade Federal do Amazona's IRB in Brazil. Individuals with T2DM were evaluated in their homes (n = 4,318,325). The variables were sex, age, skin color, education level; health-related variables such as body mass index, nutritional behavior, and frequency of physical activity. Measures related to patient self-management behaviors over the past 6 months (Patient Activation Measure - PAM-13) were included in the survey. Descriptive and frequency data are presented as mean (standard deviation (SD)) or numeric percentage). Statistical testing was performed using IBM SPSS V.26, and a p-value of < 0.050 showed significance. Activation levels were dichotomized into low activation (Levels 1 and 2) and high activation (Levels 3 and 4). A multivariate linear model assessed the association between the PAM-13 score and the following variables: age, sex, BMI, skin color, number of comorbidities, burden of symptoms, and number of medications. Results Logistic regression analyses indicated a statistically significant association between sex, age, education, self-rated health, and general satisfaction with life. men were 43% more likely to score lower levels (p < 0.001). The results also indicated that advanced age had lower PAM levels (p < 0.001). Participants with fewer years of education were 44% more likely to have lower levels of PAM (p = 0.03). Worse self-rated health (p < 0.001) and lower general life satisfaction (p = 0.014) were associated with lower PAM levels. Conclusions Low patient activation was associated with worse sociodemographic, health, and psychological conditions in the Amazon population. The low level of patient activation observed in this sample highlights an important impediment to diabetes disease management/self-management in disadvantaged populations.